Informatics research using publicly available pathology data - Jules J Berman (Elsevier, 2011)
The day has not arrived when pathology departments freely distribute their collected anatomic and clinical data for research purposes. Nonetheless, several valuable public domain data sets are currently available, from the U.S. Government. Two public data sets of special interest to pathologists are the SEER (the U.S. National Cancer Institute's Surveillance, Epidemiology and End Results program) public use data files, and the CDC (Center for Disease Control and Prevention) mortality files. The SEER files contain about 4 million de-identified cancer records, dating from 1973. The CDC mortality files contain approximately 85 million de-identified death records, dating from 1968. This editorial briefly describes both data sources, how they can be obtained, and how they may be used for pathology research.